How does Video Assistant Referee (VAR) modify the game in elite soccer? - Carlos, L. P.; Ezequiel, R.; Anton, K. (International Journal of Performance Analysis in Sport, 2019)
The aim of this study was to examine how the introduction of the VAR system influenced the play in elite soccer. The sample consists of 1024 matches played in the Italian Serie A and the German Bundesliga league during the seasons before and after the implementation of the VAR system. The following variables were recorded for each match: Fouls, Goals, Offsides, Penalties, Playing time in the first half, Playing time in the second half, Total Playing time, Red cards and Yellow cards. Match statistics were retrieved from the website of "Whoscored" (www.whoscored.com). A generalized linear model and a pairwise z-tests were used to compare seasons before and after the implementation of the VAR. There was a decrease in the number of offsides, fouls and yellow cards after the implementation of the VAR. Meanwhile, there was an increase in the number of minutes added to the playing time in the first half and the full game, but not in the second half. These findings may help coaches, players and managers to better understand the effects of the VAR system on professional soccer and to identify strategies to improve refereeing during matches.